2023
DOI: 10.1186/s12913-023-09050-1
|View full text |Cite
|
Sign up to set email alerts
|

A landscape assessment of the use of patient reported outcome measures in research, quality improvement and clinical care across a healthcare organisation

Abstract: Background Patient reported outcome measures (PROMs) can be used by healthcare organisations to inform improvements in service delivery. However, routine collection of PROMs is difficult to achieve across an entire healthcare organisation. An understanding of the use of PROMs within an organisation can provide valuable insights on the purpose, scope and practical considerations of PROMs collection, which can inform implementation of PROMs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Benchmarking is a valuable approach that can be used to optimize patient journey and improve healthcare provision strategies [ 35 , 36 ]. However, there are only a few examples for the use of patient-reported measures by the stakeholders for these aims [ 39 ]. We managed to capture and identify specific elements of the patient journey as potential objects for improvement at the national healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benchmarking is a valuable approach that can be used to optimize patient journey and improve healthcare provision strategies [ 35 , 36 ]. However, there are only a few examples for the use of patient-reported measures by the stakeholders for these aims [ 39 ]. We managed to capture and identify specific elements of the patient journey as potential objects for improvement at the national healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…The digital approach to collecting patient-reported measures and integrating them into the E-systems is still an innovative form of patient engagement. A recent large meta-analysis of patient-reported outcome measures implementation in research and clinical use revealed that, in most of the cases, paper forms were still used with only a very small part collected purely electronically or combining both methods [ 39 ]. Age-related digital illiteracy and, in some cases, access to the Internet, had been highlighted by the studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to consumer involvement is the incorporation of a related program of work, implementing routine collection of Patient Reported Outcome Measures (PROMS) into Peninsula Health for incorporation into the Healthy Ageing Data Platform [ 15 ]. This activity will ensure that data obtained from consumer, and not just clinician perspectives are available within the Platform.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the PRO-HF Trial research, 5 there is growing interest about incorporating them in routine clinical care. 2,[6][7][8][9][10] To that extent, multiple organizations, including the American Heart Association and the Centers for Medicare and Medicaid Services, have introduced quality measures promoting routine PRO assessment in clinical care, including for patients with heart failure (HF). [11][12][13] The HF community has shown increasing interest in incorporating PROs into clinical care.…”
Section: Sandhu Et Almentioning
confidence: 99%